MUKOP SAGAI: MENAKAR KADAULATAN PANGAN ORANG SAREREIKET DI SIBERUT SELATAN, KEPULAUAN MENTAWAI - Erwin Erwin; Ade Irwandi; Robi Mitra (Social Welfare Study Program, 2022)
Abstract. The problem of food is indeed a very complicated problem to discuss and is a fundamental matter for humans. Because it involves survival and survival and is related to other problems. As a result of the Covid-19 pandemic, the government is again planning to re-utilize sago as a staple food that needs to be developed through the Nusantara Sago Week 2020. Sago contributes to the fulfillment of food in Indonesia, not only rice and can provide economic opportunities. In the Mentawai Islands, is an area that has a lot of land and sago plants. However, this has not been ignored for a long time because many programs from the government are contradictory and have resulted in sago land and the Sarereiket community being pressured. So that their access to food, which is mainly sago, has begun to be disrupted. This study uses an ethnographic approach with interpretation analysis. So that they can question and answer doubts about the phenomenon of food problems in South Siberut, especially for the Sarereiket people. Government intervention through policies and programs that lead to food causes harm and duality to the Sarereiket people. So they are in a dilemma and trapped in the simalakama trap of